The situation of digitalization of inclusive education and the problems in Armenia - Asatryan, Samvel
There is no doubt to state that the 21st century is the century of digital information and endless technological possibilities. A century when thousands of new high-tech mechanisms are being created at an incredible speed, the main goal of which is the most comfortable and convenient life for people. Digital technologies have filled almost all spheres of human life and activity. Today, a large number of countries in the world have a successful experience in the introduction and use of digital technologies in education. Undoubtedly, they play a special and important role in the education of people with disabilities, the disabled and people with special needs. The exercise by persons with disabilities of the right to education, a fundamental human right, is fraught with several challenges. The lack of necessary conditions for full participation in the educational process that meet the individual needs and abilities of students, as well as the use of insufficiently effective teaching methods, leads to the fact that the youngest people with disabilities cannot get a good education and profession. The inaccessibility of education is one of the main reasons preventing the full inclusion of disabled people in the life of modern society. Results of the study indicate that the correct use of the capabilities of modern digital technologies by the teacher will contribute to effective work to overcome violations of psychophysical development.
Keywords: Education